2018
DOI: 10.1111/bjd.15867
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis for most patients with pustular skin disease remains elusive

Abstract: SummaryBackground Rare variants in the genes IL36RN, CARD14 and AP1S3 have been identified to cause or contribute to pustular skin diseases, primarily generalized pustular psoriasis (GPP). Objectives To better understand the disease relevance of these genes, we screened our cohorts of patients with pustular skin diseases [primarily GPP and palmoplantar pustular psoriasis (PPP)] for coding changes in these three genes. Carriers of single heterozygous IL36RN mutations were screened for a second mutation in IL36R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
115
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 29 publications
4
115
1
3
Order By: Relevance
“…It is possible that maternal relatives simply have a common haplotype at IL36RN that is functioning as a hypomorphic allele, as described in TBX6 . However, in a recent study, rare non‐coding IL36RN variants were not identified in 11 heterozygous carriers …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that maternal relatives simply have a common haplotype at IL36RN that is functioning as a hypomorphic allele, as described in TBX6 . However, in a recent study, rare non‐coding IL36RN variants were not identified in 11 heterozygous carriers …”
Section: Discussionmentioning
confidence: 99%
“…However, single heterozygous variants of the IL36RN gene in some cases with GPP and homozygous variants in unaffected individuals indicate a complex mode of inheritance instead of a recessive Mendelian inheritance in GPP with IL36RN variants. Moreover, segregation analyses confirm that the probands have inherited the disease allele of IL36RN or AP1S3 from an unaffected parent, which suggests the presence of unidentified environmental triggers, a modifier locus or an oligogenic inheritance . Mossner et al .…”
Section: Introductionmentioning
confidence: 91%
“…The study, which is published in this issue of the BJD , confirmed the presence of substantial genetic heterogeneity. This was especially marked in PPP, where > 90% of cases were mutation negative . While this figure is slightly lower in other surveys, there is no doubt that further gene identification studies will be required to illuminate the genetic landscape of PPP and improve its molecular diagnosis.…”
mentioning
confidence: 86%
“…is the thorough analysis of 11 individuals harbouring a single IL36RN mutation. It showed that none of these patients carried an exon deletion or duplication alongside the identified missense mutation . This strongly suggests the presence of modifier alleles at other loci.…”
mentioning
confidence: 91%
See 1 more Smart Citation